Goal Congruence: A Humanity Approach in Exercising Power and Influence to Transform Individual Interest into Coordinated Activities - Suwaldiman Suwaldiman (Universitas Islam Indonesia, 2004)
This paper discusses the main tasks of managers in exercising their power and in-fluence to transform the individual interest into coordinated activities that accomplish valu-able ends. It is argued that the humanity approach is very effective in exercising power and in-fluence. The nature of goal congruence, humanity approach in exercising power and influ-ence, reward versus punishment, management control by participation, and trust and self-control are examined. The success of goal congruence depends on whether managers perform and exercise their power and influence by totalitarian approach or humanity approach. Hu-manity approach suggests that in exercising power and influence, managers should develop humanitarian administrative customs. A humanity approach encourages managers to exercise their power and influence to create a workplace climate of open relationships, trust and hon-esty. If this method can be well applied the result will benefit all around, the organization, the managers, and the employees. Humanity approach suggests that management control should be reward oriented instead of punishment oriented because reward is more effective than pun-ishment to achieve goal congruence. Plans and budgets seem to be more effective tools to con-trol goal congruence if subordinate managers or staffs participate actively with their superior in the process of arriving plans and budgets. Finally, humanitarian control system suggests that trust should be delivered to subordinate managers and staffs in which they can perform self-control through delegated control systems and power distribution. Human beings tend to perform better jobs when they are controlled by themselves rather than by superior managers or other surveillance. Therefore, the humanity approach is very effective in exercising power and influence instead of totalitarian approach.